Local conformations and heterogeneities in structures and dynamics of isotactic polypropylene adsorbed onto carbon fiber. (16th January 2023) - Huang, Zhixing; Bajaj, Yashasvi; Carrillo, Jan-Michael Y.; Nakanishi, Yohei; Uchida, Kiminori; Mita, Kazuki; Yamada, Takeshi; Miyazaki, Tsukasa; Sumpter, Bobby G.; Endoh, Maya; Koga, Tadanori
Abstract: Carbon fiber (CF) reinforced polymers (CFRPs) have experienced widespread use in various industries. One of the most important parameters that controls the macroscopic property of CFRPs is the interface between a polymer matrix and CF. There is growing evidence to suggest the formation of a bound polymer layer (BPL), i.e., polymer chains that physically adsorb on a filler surface. However, this interface is always in contact with the thicker part of a polymer matrix, rendering its understanding a difficult task. Therein, we use CF-reinforced isotactic polypropylene (iPP) as a rational CFRP. To characterize the BPL on the CF surface, we extracted it from the CFRP using solvent-rinsing with p-xylene. The physical and thermal properties of the BPL were characterized by differential scanning calorimetry and thermogravimetric analysis, while its microscopic structures and dynamics were probed by small-angle neutron scattering and quasi-elastic neutron scattering (QENS) techniques. Subsequently, we employed atomistic molecular dynamics (MD) simulations to complement the QENS results above the bulk melting temperature and reveal details that were experimentally inaccessible. We observed that the degree of crystallinity of the BPL was quite lower than the bulk, while the melting temperature of the BPL remained the same as the bulks. Within the given length and time scales probed by QENS and MD, we also observed that most of the bound chains were mobile, with the formation of a high-density region (less than 1 nm in thickness) near the CF surface. The segmental dynamics of the bound chains probed by both QENS and MD were also much faster than those of the free chains, possibly due to the presence of a free surface region at the topmost surface of the BPL. Furthermore, the MD results demonstrated that the backbone chains and side groups lie nearly flat on the CF surface, which is the driving force for the flattening process of the iPP BPL to overcome the conformational entropy loss in the total free energy. Graphical abstract: Image 1 Highlights: The interface between carbon fiber (CF) and polypropylene (iPP) is investigated. The integrated experimental and computation approaches are employed. Backbone chains and side groups of iPP on CF lie nearly flat on the CF surface. The local heterogeneities in the buried structures and dynamics are unraveled.